Education Policies of the Organization for Economic Cooperation and Development: achievements and pending challenges in four Latin American nations (1991-2021): Políticas educativas de la Organización para la Cooperación y el Desarrollo Económico: logros y retos pendientes en cuatro naciones latinoamericanas (1991 – 2021) (Papeles, 2021)
The Organization for Economic Co-operation and Development (OECD) is an international institution founded in 1961, which has guided the formulation, management, and implementation of public policies among the 38 countries registered (until 2021). Its preponderance as a consulting and certifying body has made its reports mandatory references for the governments of the four Latin American countries of OCDE: Chile, Colombia, Mexico, and Costa Rica, especially in the education field. In this sphere, OEDC has proposed guidelines and measures that have been partially or totally reproduced in school systems of these countries, offering different results, and generating certain consensus in the actions of educational authorities, although also giving rise to controversies regarding the functionality of such guidelines in the contexts of these nations.This article reviews the role of the OECD as an institution that promotes education in five guidelines: school coverage, teacher professionalization, skill development, educational evaluation, and quality accreditation. To do this, it is based on the reports of this organization in last thirty years (1991 - 2021) for the four Latin-American member of OECD. Likewise, a recount is made of the plans and programs of the governments of these four countries   to implement their recommendations, as well as their achievements and pending aspects.  Finally, a critical assessment is made of scope that the application of these guidelines has had on improving their education.
Keywords: public policies; OECD; Latin America; education